2010
DOI: 10.1017/s0022215110001106
|View full text |Cite
|
Sign up to set email alerts
|

Vocal quality of patients treated for laryngeal tuberculosis, before and after speech therapy

Abstract: Following treatment of laryngeal tuberculosis, the incidence of dysphonia was very high. Speech therapy improved patients' vocal quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…We did not find in the literature a single report on voice disorder assessment in LTB patients with active lesions. The papers published report functional alterations after medical treatment [ 13 , 15 ]. Considering that voice disorders were still present in more than 80% treated LTB cases [ 13 ], we can assume that this alteration begins during the active phase of the disease and is perpetuated due to the LTB lesion scarring process or by functional adjustment mechanisms developed during the phase of voice functional limitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not find in the literature a single report on voice disorder assessment in LTB patients with active lesions. The papers published report functional alterations after medical treatment [ 13 , 15 ]. Considering that voice disorders were still present in more than 80% treated LTB cases [ 13 ], we can assume that this alteration begins during the active phase of the disease and is perpetuated due to the LTB lesion scarring process or by functional adjustment mechanisms developed during the phase of voice functional limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The papers published report functional alterations after medical treatment [ 13 , 15 ]. Considering that voice disorders were still present in more than 80% treated LTB cases [ 13 ], we can assume that this alteration begins during the active phase of the disease and is perpetuated due to the LTB lesion scarring process or by functional adjustment mechanisms developed during the phase of voice functional limitation. It is possible that speech-language guidance given to patients during LTB treatment is able to prevent the compensatory mechanisms that lead to the perpetuation of voice disorders, thus restoring the quality of communication and reducing vocal and social impacts of the disease, even before the end of medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Ruas et al also reported improved voice quality and maximum phonation time and Improved S/Z ratio in patient with tuberculosis following voice therapy. 20 In this study, there was a predominance of normal group over the asthma and tuberculosis group with respect to all variables compared. Lack of confounding factors like age, sex and severity of disease are mentioned as the limitations of this study.…”
Section: Discussionmentioning
confidence: 54%
“…19 Ruas et al found improved maximum phonation duration and S/Z ratio in patient with tuberculosis after speech therapy. 20 Fagundes et al found improved maximum phonation duration in patient with tuberculosis by four second following speech therapy. 21 According to the literature, pulmonary tuberculosis can cause a reduction in loudness since the expiratory air volume is the source of the aerodynamic energy for phonation.…”
Section: Discussionmentioning
confidence: 97%